(untitled) (International Journal of Engineering and Computer Science, 2024)
This study investigates the impact of AI on human-computer interaction patterns among Nigerian children, focusing on accessibility, usage, and educational outcomes. The research encompasses both parental and teacher perspectives, analyzing demographic data and AI technology integration. Results reveal significant discomfort among parents regarding unsupervised AI use by children, yet highlight the potential benefits of AI in enhancing academic performance and motivation. Teachers report varied frequency in incorporating AI into lessons, influenced by accessibility and educational context. Cultural and social factors play a crucial role in AI adoption, presenting challenges such as device availability and internet access. This comprehensive analysis underscores the need for balanced AI integration, considering both educational advantages and potential discomforts, to optimize learning experiences and foster responsible AI usage in academic settings.